2017
DOI: 10.1051/epjconf/201715305020
|View full text |Cite
|
Sign up to set email alerts
|

Activation calculation for the dismantling and decommissioning of a light water reactor using MCNP™ with ADVANTG and ORIGEN-S

Abstract: Abstract. The decommissioning of a light water reactor (LWR), which is licensed under § 7 of the German Atomic Energy Act, following the post-operational phase requires a comprehensive licensing procedure including in particular radiation protection aspects and possible impacts to the environment. Decommissioning includes essential changes in requirements for the systems and components and will mainly lead to the direct dismantling. In this context, neutron induced activation calculations for the structural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…-Identification of isotopic composition, contamination level in spent fuel, structures, and components -Identification of the nature and extent of remedial actions and decontamination methods -Facilitating the preparation for decommissioning Decommissioning project is divided into several phases to help personnel with learning and integrating their experience during work. This method assists with reduction of time while supporting safety and radiation protection, also, with additional information of radiological inspections, it contributes to the waste management process as it is required for waste characterization [1][2][3][4][5][6][7]. As a learnt lessons, it was found that to improve decommissioning project schedule, the removal of large components should be applied to ex-situ cutting as an alternative of in-situ cutting; that approach consist of [8][9]: Decontamination and removed component can be made outside the site by a service provider.…”
Section: Introductionmentioning
confidence: 99%
“…-Identification of isotopic composition, contamination level in spent fuel, structures, and components -Identification of the nature and extent of remedial actions and decontamination methods -Facilitating the preparation for decommissioning Decommissioning project is divided into several phases to help personnel with learning and integrating their experience during work. This method assists with reduction of time while supporting safety and radiation protection, also, with additional information of radiological inspections, it contributes to the waste management process as it is required for waste characterization [1][2][3][4][5][6][7]. As a learnt lessons, it was found that to improve decommissioning project schedule, the removal of large components should be applied to ex-situ cutting as an alternative of in-situ cutting; that approach consist of [8][9]: Decontamination and removed component can be made outside the site by a service provider.…”
Section: Introductionmentioning
confidence: 99%